Heat‐shock proteins as dendritic cell‐targeting vaccines – getting warmer. Issue 4 (2nd July 2013) - McNulty, Shaun; Colaco, Camilo A.; Blandford, Lucy E.; Bailey, Christopher R.; Baschieri, Selene; Todryk, Stephen
Summary Heat‐shock proteins (hsp) provide a natural link between innate and adaptive immune responses by combining the ideal properties of antigen carriage (chaperoning), targeting and activation of antigen‐presenting cells (APC), including dendritic cells (DC). Targeting is achieved through binding of hsp to distinct cell surface receptors and is followed by antigen internalization, processing and presentation. An improved understanding of the interaction of hsp with DC has driven the development of numerous hsp‐containing vaccines, designed to deliver antigens directly to DC. Studies in mice have shown that for cancers, such vaccines generate impressive immune responses and protection from tumour challenge. However, translation to human use, as for many experimental immunotherapies, has been slow partly because of the need to perform trials in patients with advanced cancers, where demonstration of efficacy is challenging. Recently, the properties of hsp have been used for development of prophylactic vaccines against infectious diseases including tuberculosis and meningitis. These hsp‐based vaccines, in the form of pathogen‐derived hsp–antigen complexes, or recombinant hsp combined with selected antigens in vitro, offer an innovative approach against challenging diseases where broad antigen coverage is critical.